Effects of low, moderate, and high-intensity aquatic exercise on joint edema in induced rat knee arthritis - Alline Mardegan Mioto; Daniel Fernando dos Reis; Thiago Alves Garcia; Guilherme Akio Tamura Ozaki; Iara Buriola Trevisan; Rodrigo Metzker Pereira Ribeiro; Robson Chacon Castoldi; José Carlos Silva Camargo Filho (ABCS Health Sciences)
Introduction: Arthritis has prompted interest in using physical exercise as therapy. This study assesses the effects of low-, moderate-, and high-intensity exercise on induced arthritis in male Wistar rats. Objective: To evaluate the impact of low-, moderate-, and high-intensity physical exercise on induced arthritis. Methods: Twenty 60-day-old rats were divided into 5 groups: Control Group Arthritis (GCA), Control Group Placebo (GCP), Group Low Physical Activity (GL), Group Moderate Physical Activity (GM), and Group Intense Physical Activity (GI). The physical activity groups received intra-articular injections of Zymosan in the right knee, followed by aquatic activity, swimming with a dorsal load for 30 minutes, 4 times weekly, for five weeks. Exercise intensity varied: GL 1%, GM 5%, GI 15% of body weight. At the end of the 5th week euthanasia was performed, and soleus muscles were histologically. Group comparisons: one-way ANOVA with Tukey or Kruskal-Wallis with Dunn's post-test, contingent on data homogeneity Levene test. Weight changes: Student’s T-test or ANOVA for repeated measurements, with Bonferroni's post-test for inter-week and first and last-week comparisons within each group. Results: There were no significant differences in inflammatory edema before or after exercise in joint diameter analysis. GI exhibited decreased inflammatory edema in the 3rd week post-activity. GM showed a substantial decrease in the 4th week compared to GL and GI. Post-intervention inflammation did not differ significantly among groups. Conclusion: Varying exercise intensities did not harm any group-induced arthritis in rats.